2016
DOI: 10.1002/ase.1638
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and satisfaction of two optional cadaveric dissection courses: A 3‐year prospective study

Abstract: Teaching time dedicated to anatomy education has been reduced at many medical schools around the world, including Nova Medical School in Lisbon, Portugal. In order to minimize the effects of this reduction, the authors introduced two optional, semester-long cadaveric dissection courses for the first two years of the medical school curriculum. These courses were named Regional Anatomy I (RAI) and Regional Anatomy II (RAII). In RAI, students focus on dissecting the thorax, abdomen, pelvis, and perineum. In RAII,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 49 publications
(74 reference statements)
3
48
0
2
Order By: Relevance
“…This advantage was largest in the second year of the curriculum during assessment of ability to apply gastrointestinal-reproductive anatomy and neuroanatomy knowledge. This academic advantage of dissection is consistent with recent studies objectively demonstrating improvements in knowledge as a result of optional anatomy dissections (Ramsey-Stewart et al, 2010;Pizzimenti et al, 2016;Rae et al, 2016;Pais et al, 2017). In addition, another study indicated that the quality of dissection has a positive association with assessment performance (Hofer et al, 2011;Nwachukwu et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This advantage was largest in the second year of the curriculum during assessment of ability to apply gastrointestinal-reproductive anatomy and neuroanatomy knowledge. This academic advantage of dissection is consistent with recent studies objectively demonstrating improvements in knowledge as a result of optional anatomy dissections (Ramsey-Stewart et al, 2010;Pizzimenti et al, 2016;Rae et al, 2016;Pais et al, 2017). In addition, another study indicated that the quality of dissection has a positive association with assessment performance (Hofer et al, 2011;Nwachukwu et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…This de‐emphasis of cadaveric dissection in medical schools has been described in the United States (Drake et al, ), Canada (Ovsenek, ), the United Kingdom (Chapman et al, ), Europe (Pais et al, ), and Australia and New Zealand (Craig et al, ; Moscova et al, ; Bouwer et al, ). Notably, this trend is common to both undergraduate entry medical schools (Ovsenek, ) as well as medical schools where graduate‐level entry is more common (Craig et al, ; Bouwer et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, a debate about the teaching of anatomy has focused on a worldwide steady decline of allocated teaching time (Moxham et al, ; Pais et al, ), the devaluation of the instructors' pedagogical commitment (Craig et al, ), the extent of the curriculum's reduction policy (Craig et al, ; Yammine, ), and the ongoing de‐emphasis on traditional teaching methods in favor of new interactive and integrative pedagogical approaches (Johnson et al, ; Drake et al, ). One of the consequences of this is that the reduction in the number of contact hours allocated to gross anatomy in integrated curricula is thought to have led to insufficient anatomical knowledge among students (McLachlan et al, ; Fraher and Evans, ; Drake et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, offering additional optional courses has been suggested as feasible method to counteract curricular reductions in anatomy education (Winkelmann, ). Recently, two optional courses of 28 hours each have been reported from Portugal, which were highly valued by the students, but to a lower degree with regard to their articulation with the pre‐existing curriculum (Pais et al, ).…”
Section: Introductionmentioning
confidence: 99%